Participatory risk assessment: a new approach for safer food in vulnerable African communities - Grace, Delia; Randolph, Thomas F.; Olawoye, J.; Dipelou, M.; Kang'ethe, Erastus K. (Informa UK Limited, 2008)
Women play the major role in food supply in developing countries, but too often their ability to feed their families properly is compromised; the result is high levels of food-borne disease and consequent limited access to higher-value markets. We argue that risk-based approaches - current best practice for managing food safety in developed countries - require adaptation to the difficult context of informal markets. We suggest participatory research and gender analysis as boundary-spanning mechanisms, bringing communities and food-safety implementers together to analyse food-safety problems and develop workable solutions. Examples show how these methodologies can contribute to operationalising risk-based approaches in urban settings and to the development of a new approach to assessing and managing food safety in poor countries, which we call 'participatory risk analysis'.